The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1029/2021gl096302
|View full text |Cite
|
Sign up to set email alerts
|

Parker Solar Probe Imaging of the Night Side of Venus

Abstract: Although Venus is the brightest planet in the sky, its surface was long a mystery due to the opacity of its thick atmosphere. Optical images of the planet show a featureless white disk, dominated by scattered sunlight from the impenetrable atmosphere. Radar imaging from Earth provided the first means to see the surface (e.g., Goldstein et al., 1976;Rogers & Ingalls, 1969), but detailed mapping had to await the arrival of orbiting spacecraft with radar capabilities, particularly Magellan (e.g., Solomon et al., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
(70 reference statements)
1
18
0
Order By: Relevance
“…Amateur observations can play an important role especially when used complementary to professional ones. Moreover, systematic monitoring by amateurs can trigger, and of course, support coordinated observing campaigns, such as the next campaigns of observations coordinated with Akatsuki (http://pvol2.ehu.eus/bc/Venus/, accessed on 15 February 2021) of Venus flybys of NASA's PARKER [49] on 21 August 2023 and 6 November 2024. The professional-amateur collaboration offers an invaluable resource in the advance of our understanding of the atmosphere of Venus.…”
Section: Discussionmentioning
confidence: 99%
“…Amateur observations can play an important role especially when used complementary to professional ones. Moreover, systematic monitoring by amateurs can trigger, and of course, support coordinated observing campaigns, such as the next campaigns of observations coordinated with Akatsuki (http://pvol2.ehu.eus/bc/Venus/, accessed on 15 February 2021) of Venus flybys of NASA's PARKER [49] on 21 August 2023 and 6 November 2024. The professional-amateur collaboration offers an invaluable resource in the advance of our understanding of the atmosphere of Venus.…”
Section: Discussionmentioning
confidence: 99%
“…In Vourlidas et al (2016) the WISPR-I and WISPR-O passbands were given as 490-740 nm and 475-725 nm, respectively. However, in a recent study of the WISPR detectors' response to the Venus nightglow, Wood et al (2022) found that their sensitivity (although reduced) extended farther into the red, up to 800 nm (for both telescopes). The angular fields of view (FOVs) are 40°and 50°elongation in the radial direction for WISPR-I and WISPR-O, respectively.…”
Section: Observations and Methodologymentioning
confidence: 95%
“…Most recently, Stenborg et al (2022) showed that a dust depletion zone exists, beginning at ∼19 R e and ending at ∼5 R e , at which point the dust-free zone begins. Other significant observations using WISPR have been the observations of the surface of Venus (Wood et al 2022), of dust in the orbit of comet/asteroid 3200 Phaethon (Battams et al 2020), of excess dust along the orbit of Venus (Stenborg et al 2021), of CMEs (Rouillard et al 2020;Hess et al 2020;Liewer et al 2021;Wood et al 2021;, and of fine-scale structure in coronal streamers (Poirier et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These reports were dismissed as optical illusions (e.g., Sheehan et al 2014). However, glimpsing some thermal emission from the night side (Sheehan et al 2014) or O2 airglow at wavelengths of ~0.45-0.55 μm with the human eye is perhaps possible (Wood et al 2022). Until the mid-20th century, observations of Venus had not advanced much from prehistory.…”
Section: Pre-1920s Views Of Modern Venusmentioning
confidence: 99%
“…Finally, PSP returned some of the most striking images of Venus ever taken at visible wavelengths (Figure 3). During flybys of Venus in 2020 and 2021, the Wide-Field Imager for Parker Solar Probe (WISPR) observed the nightside of Venus (Wood et al 2022). WISPER was designed to study the solar wind at wavelengths from ~0.5-0.8 μm.…”
Section: Parker Solar Probementioning
confidence: 99%